A Hospital-Based Study of Iodine Nutrition Status of Breastfeeding Mothers in Bangladesh. (7th October 2019) - Naznin, Jobaida; Fariduddin, Mohammad; Hasan, Mashfiqul; Atiqur-Rahman, Mohammad; Sultana, Nusrat; Anowar-Hossain, Mohammad; Chowdhury, Sharmin; Hasanat, Muhammad Abul
Abstract : Adequacy of iodine nutrition status in breastfeeding mothers is vital in preventing iodine deficiency disorder (IDD) in neonates and children. The aim of the study was to assess urinary iodine status in breastfeeding mothers attending Bangabandhu Sheikh Mujib Medical University (BSMMU) hospital in Bangladesh. In this cross-sectional study carried out from January 2014 to January 2015, urinary iodine (UI; μ gm/L) level of 266 mothers (age 26.6 ± 4.7 years (mean ± SD), exclusively breastfeeding: 132 and nonexclusively breastfeeding: 134), recruited on consecutive basis from BSMMU outdoor and indoor, were measured in spot urine following the wet digestion method. Median UI in the participants was 298.6 (interquartile range, IQR 206.6–454.9) μ gm/L and only 6.4% lactating mother had low UI (i.e. <100 μ gm/L). There was no difference of median UI in relation to exclusive or nonexclusive breast feeding, presence of goiter, parity, and age of breastfed baby (p = ns for all ). But median UI was higher in older subjects (≥30 years vs. <30 years: 364.4 (228.4–529.9) vs. 283.7 (205.4–434.0); median (IQR)p = 0.040 )), with good socioeconomic condition (good vs. average or less: 328.2 (243.8–510.0) vs. 274.4 (200.0–433.3); median (IQR);p = 0.020 ), and in those who are aware regarding the importance of iodine (aware vs. unaware: 316.6 (225.2–506.3) vs. 270.1 (196.0–407.2); median (IQR);p = 0.018 ). The proportion of participants with UI < 100 μ gm/L was similar in all the groups. Logistic regressions to predict deficient UI status revealed none of the variables to be an independent predictor. This study indicates that deficient iodine nutrition status in Bangladeshi breastfeeding mothers is not frequent at present.